Covid-19 vaccine efficacy and Russian public support for anti-pandemic measures - Ekaterina Borisova; Denis S. Ivanov (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
In this study, we use random assignment of vignettes that feature optimistic and pessimistic scenarios with respect to vaccine safety and efficacy on a sample of roughly 1,600 Russians in order to gauge public support for anti-pandemic measures under various scenarios. Negative information on vaccine safety and efficacy reduces support for the anti-pandemic measures among individuals who fear Covid-19 and were initially supportive of government restrictions. These individuals tend to be old, and therefore vulnerable to Covid-19, and politically active. This loss of support is strongest for economically costly measures such as banning of large gatherings and the shuttering of non-essential businesses. Mask-wearing, which involves only minor costs, finds broad acceptance. We interpret the reactions in light of adaptation, fatigue over Covid-19 restrictions, and fatalism. The political consequences of non-pharmaceutical measures to deal with a pandemic include loss of public support over time, erosion of trust in government, and political backlash.
URN:NBN:fi:bof-202107051319
Keywords: I12; I18; C93; 330; Covid-19; vaccine; non-pharmaceutical measures; anti-pandemic restrictions; lockdown; anxiety